Enhancing The Service Quality of The Tour and Travel SME By Integrating Servqual Dimensions, Kano Model, and Fishbone Diagram - Hidayatullah, Taufiq Asy'ari; Wurjaningrum, Febriana (Southeast Asian Business Review, 2023)
Transportation services are one of the prominent sectors in the movement of the economy. The current transportation system should be arranged in an integrated manner in a single national-scale system to balance the readiness of transportation services and public needs. A proper transportation system can lead to the realization of the goal of building a firm infrastructure and sustainable-inclusive industrialization in the future. Qualitative case study of an SME in Indonesia using the Servqual, Kano, and Fishbone diagram. These three methods can analyze the relationship between quality attributes and determine the factors that influence the quality of a product or service. This study obtained analysis results using the Servqual method that six attributes have the highest gap between reality and expectations. Based on the results using the Kano Model, three classification categories include ten attributes, namely (1) Category O (One Dimensional), (2) Category R (Reverse), and (3) Category Q (Questionable). In addition, analysis of 10 service attributes that are priorities for improvement using the Fishbone diagram produces four main factors (Man, Machine, Environment, and Method) that influence the quality of SME services. This study enriches reference material for considerations in improvement efforts of service attribute weaknesses for transportation service SMEs.